Geometric Transformations Embedded into Convolutional Neural Networks - Tarasiuk, Paweł; Pryczek, Michał (Journal of Applied Computer Science, 2016)
This paper presents a novel extension to convolutional neural networks. While CNNs are known for invariance to object translation, changes to the other parameters could make the image recognition tasks diffcult – that includes rotations and scaling. Some improvement in this area could be achieved with embedded geometric transformations used inside the CNNs. In order to provide a practical solution, which allows fast propagation and learning of the modified networks, “fast geometric transformations” are introduced.